Contrato de locação em Shopping Center - Gershenson, Andrea Sirotsky (2014)
This study analyzes the lease contract of a specific type of business organization: the Shopping Mall. We will analyze the characteristics of this kind of development and other aspects that make it a complex and unique structure and which also make it distinct from other commercial centers. Even after the Lease Law was sanctioned (Law 8.245/91), which defined the relationship between the entrepreneur and the shopkeeper as a location, it is possible to consider the peculiarities of this kind of business and notice that there is still controversy about the legal nature of this kind of contract. Thus, we will study the doctrinal positions on the legal nature of the mall, and later qualify it as a typical or atypical contract. The legal business will be contextualized within the modern view of contract law, analyzing its main principles, in particular social function, equity and good faith. We will analyze the Mall contract and its peculiar clauses under the perspective of those paradigms. We will then approach the subject of how the termination of this kind of contract would work in case of breach of its provisions, and its chances for revision or alteration. Finally, this study will weave considerations about termination or renewal actions as far as the lease contract in shopping malls is concerned